2020
DOI: 10.1021/acs.est.0c00060
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption of Pb(II) on an Annealed Hematite (1102) Surface: Evidence from Crystal Truncation Rod X-ray Diffraction and Density Functional Theory

Abstract: The Pb­(II)-binding mechanism on an annealed hematite (102) surface was studied using crystal truncation rod (CTR) X-ray diffraction coupled with density functional theory (DFT) calculations. The best fit CTR model suggested that Pb­(II) sorbed selectively to one type of edge-sharing surface site (ES 2 ) over two other potential surface sites. From the best fit model structure, it was found that the Pb surface complex species forms a trigonal pyramid geometry. The base consists of three oxygen groups, two of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
(116 reference statements)
0
11
0
1
Order By: Relevance
“…The importance of integrating surface science with direct sorption experiments was underscored by a recent publication by Qiu et al, who studied lead sorption on the full-termination {012} facet of cut and polished hematite. 74 In a prior study, the same research group found that, on the half-layer termination, Pb 2+ bound at two distinct FeO 6 octahedral edges to form two different bidentate, edge-sharing structures. 73 However, on the full-layer termination, only one of these structures was found because the reorientation of Fe and O in the half-layer termination meant that the binding geometry (i.e., bond angles and lengths) of the second structure were too energetically unfavorable.…”
Section: Applicationsmentioning
confidence: 98%
See 4 more Smart Citations
“…The importance of integrating surface science with direct sorption experiments was underscored by a recent publication by Qiu et al, who studied lead sorption on the full-termination {012} facet of cut and polished hematite. 74 In a prior study, the same research group found that, on the half-layer termination, Pb 2+ bound at two distinct FeO 6 octahedral edges to form two different bidentate, edge-sharing structures. 73 However, on the full-layer termination, only one of these structures was found because the reorientation of Fe and O in the half-layer termination meant that the binding geometry (i.e., bond angles and lengths) of the second structure were too energetically unfavorable.…”
Section: Applicationsmentioning
confidence: 98%
“…72 While both terminations contain singly and triply coordinated terminal oxygens, the half-layer termination also contains doubly coordinated oxygens, known to be less exchangeable. 73,74 Comparison of the reflectivity profiles suggests that the halflayer termination is the dominant termination in water but that some full-layer termination exists. 69,73,75,76 The clean {001} facet has been reported to have three different terminations: a single Fe termination, a double Fe termination, and an O termination.…”
Section: Atomic and Electronic Characteristics Of Nmo Facetsmentioning
confidence: 99%
See 3 more Smart Citations